Editor’s note - Editor (Analecta Archaeologica Ressoviensia, 2017)
We are pleased to present the 12th volume of the Analecta Archaeologica Ressoviensia journal. The previous issue, presenting studies into the Bronze Age and the Early Iron Age, was dedicated to Professor Sylwester Czopek on the 35th anniversary of his academic career. Since the 4th volume, it has been the Editing Board’s objective to publish articles that are thematically consistent and situated within the scope of archaeological interests. The articles included in the present publication focus on issues linked to broadly-termed non-invasive studies in archaeology. The included texts discuss the use of the ground-penetrating radar, the magnetometer, aerial prospection or the interpretation of data acquired during aerial scanning. Our other objective involves the preservation of the journal’s format, due to which much of the publication consists of reviews, polemical articles, conference reports and memoirs. This volume also introduces the principle of publishing articles in congress languages. We hope that this volume will meet your expectations and contribute to the further promotion of non-invasive methods in archaeology, which – in any case – are already the current standard research procedure.